Layanan Bimbingan Belajar dalam Mengurangi Kesulitan Belajar Siswa Kelas IV Sekolah Dasar - N Nelyahardi; Molia Prizunil (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
The purpose of this study was to find out the process of tutoring services in reducing learning difficulties of fourth grade students of SDN 13 / I Muara Bulian. The method of this research is descriptive qualitative research with the subject of 1 grade IV teacher. The data in this study were obtained in 3 ways; the first is by conducting observations to find out the process of giving tutoring to students in reducing learning difficulties, the second conducting interviews to find out information about tutoring services, and documentation of observations made during the learning activities taking place. The results of this study are that teachers provide tutoring services to students who have learning difficulties in order to reduce learning difficulties faced by these students. In its implementation the teacher performs several stages, namely the introduction of students who experience learning problems, efforts to help students who experience learning problems and the provision of assistance to alleviate learning problems, namely the provision of tutoring services in accordance with learning difficulties faced by students.